Ta’liim Al Munadzarah Al Lughawiyah fi Al Barlaman Al Asiyawiy li Al Ta’awwud ‘ala Al Kalam fi Nadii “Nafilah” Semarang - Moh In'ami; Syaiful Mustofa; Hamzah Asadullah (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
The aim of this research is to know the teaching of debate in a nafila, with a view to the speaking skill among the students. This research is a field study with a qualitative approach and its description is descriptive. Researchers acquire data from two sources; primary and secondary. In collecting data, by observation, interview and documentation. The method of data analysis used by researchers is the descriptive method.The researchers found that teaching linguistic debate in the Asian Parliament to accustom the speaking skill in “Navala” brings a good result in accustoming the members of the debate class to some achievements in the Arabic debate. The educational process uses a procedural approach, its strategy is a small group, each one is trained, and self-organized learning. The oral audio and discussion is its way, and its means are the video and the WhatsApp audio message.الهدف من هذا البحث هو معرفة تعليم المناظرة في نافلة مع الإطلاع على مهارة الكلام بين التلاميذ. هذا البحث دراسة ميدانية بالمدخل النوعية وصفتها الوصفي. يكتسب الباحثون البيانات من مصادرين؛الأساسية والثانوية. وجمع البيانات، بطريقة الملاحظة، المقابلة والتوثيق. أما طريقة تحليل البيانات يستخدمها الباحثون هى الطريقة الوصفية.وجد الباحثون أن تعليم المناظرة اللغوية بالبرلمان الآسيوي لتعويد مهارة الكلام في "نافلة" تأتى بنتيجة جيدة في تعويد الكلام لدي أعضاء فصل المناظرة حتى يوصلهم إلى بعض الإنجازات في المناظرة العربية. تستخدم علمية التعليم في نافلة المدخل الإجرائي، إستراتيجيتها مجموعة صغيرة، كل واحد مدرب، والتعلم الذاتي المنظمة. والسمعي الشفهى والمناقشة طريقها، ووسائلها هى الفيديو والرسالة الصوتية الوتسابية.